Rehabilitation following microfracture for chondral injury in the knee - Hurst, J. M.; Steadman, J. R.; O'Brien, L.; Rodkey, W. G.; Briggs, K. K. (Clinics in Sports Medicine, 2010)
Full-thickness chondral defects in the knee are common, and these articular cartilage lesions may present in various clinical settings and at different ages. Articular cartilage defects that extend full thickness to subchondral bone rarely - by providing a suitable environment for new tissue formation and takes advantage of the body's own healing potential. Proper surgical technique and rehabilitation improve the success rate of the microfracture procedure. The goals are to alleviate the pain and disability that can result from chondral lesions and restore joint conformity, thereby preventing late degenerative changes in the joint.